244. EXPLORING THE OPTIMAL STARTING AGE FOR ESOPHAGEAL CANCER SCREENING BASED ON DATA FROM A MULTICENTER POPULATIONS-BASED COHORT AND CANCER REGISTRY. (24th September 2022) - Chen, Ru; Dou, Lizhou; Zhou, Jiachen; Song, Guohui; Li, Bianyun; Zhao, Deli; Hua, Zhaolai; Wang, Xinzheng; Li, Jun; Hao, Changqing; Li, Yanyan; Feng, Xiang; et al.
Abstract: Although endoscopic screening has been proven to be effective in reducing the incidence and mortality of esophageal cancer, evidence is limited on the determination of starting age for individuals participating in the screening. The aim of this study is to provide evidence-based recommendations on starting age for esophageal cancer screening. We used the data from a multicenter prospective screening cohort in high-risk areas of esophageal cancer in China to explore the starting age of population-based screening. The target population was all permanent residents aged between 40 and 69 years from six centers. The hazard ratio (HR) with 95% confidence interval (CI) and number needed to screen (NNS) were compared between the screened group and the unscreened group in different age groups. The starting age of opportunistic screening for general population was analyzed based on the incidence and mortality of esophageal cancer estimated from cancer registry. The cohort analyzed in this study consisted 113340 screened and 224677 unscreened subjects. Compared with the unscreened group, significant reductions were observed in incidence and mortality in all age groups in the screened group except for the incidence in the 40–49 age group (HR = 0.94, 95%CI:0.79–1.13). There were large gaps in the effectiveness of screening for different age groups. The NNS to prevent one esophageal cancer death was 769, 198 and 63 in the 40–49, 50–59 and 60–69 age groups, respectively. Incidence and mortality of esophageal cancer in the general population attained the average at the age of 50–54 years. Postponing the starting age of endoscopic screening to 50 years might improve the effectiveness of screening in high-risk areas. Individuals with general risk could take their first endoscopic screening at the age of 50–54 years.